EXAMINING LOCAL PALESTINIAN MARKET READINESS TO ADAPT TO EXTENDED REALITY TECHNOLOGY THROUGH ACADEMIC-INDUSTRIAL PARTNERSHIP - Atawneh, Mohammad (An-Najah National University, 2024)
The rapid development of Extended Reality (XR) that consists of virtual reality (VR), augmented reality (AR), and mixed reality (MR) technology holds immense potential for various industries to revolutionize their operations. However, successful adoption of XR requires a market that is prepared to integrate this new technology. This thesis investigates the readiness of the Palestinian local market to embrace XR. This research proposes a model to assess the local market's readiness to adopt extended reality technology. The research utilized the questionnaire and interviews as quantitative and qualitative approaches, respectively. The study covered the research community, with 80 samples representing the Palestinian government as well as private institutions and companies. The researcher distributed and analysed questionnaires using the SMART-PLS program, as well as conducted manual analysis of 20 interviews with different institutions. The model consists of eight variables: training, trainees, innovation readiness, strategic readiness, and resource readiness, which are independent variables; organizational performance and industrial-academic partnership (IAP), which are intermediate variables; and the organization’s readiness to adapt to the technology of extended reality, which is a dependent variable. The study concluded that the Palestinian local market is already ready to adapt XR technology, and the interviews provided an insight into the opinions of Palestinian institutions with XR technology, the obstacles that exist, and how to overcome them through the industrial-academic partnership. The study revealed the local market's interest in XR technology across various sectors, particularly the engineering sector, despite the challenges faced by each sector, including material constraints and a shortage of qualified human resources. The study confirmed that the industrial-academic partnership will help overcome these barriers and challenges by providing training and addressing material obstacles. Accordingly, the researcher recommended establishing industrial academic partnerships, providing the necessary resources to adopt this technology in all sectors, and supporting start-up companies in this field.
بحث استعداد السوق المحلي الفلسطيني للتاقلم مع تكنولوجيا الواقع الممتد عن طريق الشراكة الأكاديمية- الصناعية